Siberian plants shift their phenology in response to climate change - Rosbakh, Sergey; Hartig, Florian; Sandanov, Denis V.; Bukharova, Evgenya V.; Miller, Tara K.; Primack, Richard B. (Global change biology, 2021)
Siberia has undergone dramatic climatic changes due to global warming in recent decades. Yet, the ecological responses to these climatic changes are still poorly understood due to a lack of data. Here, we use a unique data set from the Russian ‘Chronicles of Nature’ network to analyse the long‐term (1976–2018) phenological shifts in leaf out, flowering, fruiting and senescence of 67 common Siberian plant species. We find that Siberian boreal forest plants advanced their early season (leaf out and flowering) and mid‐season (fruiting) phenology by −2.2, −0.7 and −1.6 days/decade, and delayed the onset of senescence by 1.6 days/decade during this period. These mean values, however, are subject to substantial intraspecific variability, which is partly explained by the plants' growth forms. Trees and shrubs advanced leaf out and flowering (−3.1 and −3.3. days/decade) faster than herbs (−1 day/decade), presumably due to the more direct exposure of leaf and flower buds to ambient air for the woody vegetation. For senescence, we detected a reverse pattern: stronger delays in herbs (2.1 days/decade) than in woody plants (1.0–1.2 days/decade), presumably due to the stronger effects of autumn frosts on the leaves of herbs. Interestingly, the timing of fruiting in all four growth forms advanced at similar paces, from 1.4 days/decade in shrubs to 1.7 days/decade in trees and herbs. Our findings point to a strong, yet heterogeneous, response of Siberian plant phenology to recent global warming. Furthermore, the results highlight that species‐ and growth form‐specific differences among study species could be used to identify plants particularly at risk of decline due to their low adaptive capacity or a loss of synchronization with important interaction partners. Siberia has undergone dramatic climatic changes due to global warming in recent decades. Yet, the ecological responses to these climatic changes are still poorly understood due to a lack of data. Using a large data set of phenological records (>15,000 observations) collected at the Barguzin Nature Reserve in Siberia, we analysed long‐term (1976–2018) phenological shifts in leaf out, flowering, fruiting and senescence of 67 common Siberian plant species. We find a strong, yet heterogeneous, response of Siberian plant phenology to recent global warming, which can be partly explained by the plants' growth forms